Microcontact-printing-assisted access of graphitic carbon nitride films with favorable textures toward photoelectrochemical application - Liu, Jian; Wang, H.; Chen, Z.; Moehwald, H.; Fiechter, S.; Van De Krol, R.; Wen, L.; Jiang, L.; Antonietti, M. (Wiley - V C H Verlag GmbH & Co. KGaA, 2015)
Cooperative photoelectrochemical (PEC) conversion of solar energy into chemical fuels is considered as one of the most promising solutions to the sustainable energy needs of mankind, considering the intermittent and spatial fluctuations in the availability of sunlight on earth. The development of synthetic visible-light-driven semiconductor catalysts that functionally mimic the elegant water reduction chemistry of hydrogenase enzymes has attracted widespread interest and also created a lot of systems. Organic water oxidation catalysts based on earth-abundant elements are more promising due to low manufacturing cost, abundance, and environmental sustainability. Toward such applications, a strategy for fabricating CN films should be developed. Generally, a successful photoelectrochemical device requires not only a high surface area, but also an optimization of the morphology and quality of the film, including the contact with the conductive substrate, the film thickness, and the size of the light harvesting microstructures.